2016
DOI: 10.1097/rlu.0000000000001118
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Tumor Burden on Baseline 18F-Fluoride PET/CT Predicts Bone Marrow Failure After 223Ra Therapy

Abstract: 223Ra was beneficial and reduced the risk of death even in patients with a high skeletal tumor burden. Fluoride PET/CT is able to determine which patients will benefit from 223Ra and which will develop BMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The extent of disease graded by counting lesions did not show a significant independent association with clinical outcome. This finding is in accordance with the results of quantification of skeletal tumor burden by 18 F-fluoride PET, which performed better than visual grading for the prognostication of OS and bone marrow failure (14,22). Likewise, a small study of 14 patients with a high BSI reported short median survival after 223 RaCl 2 therapy (23).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The extent of disease graded by counting lesions did not show a significant independent association with clinical outcome. This finding is in accordance with the results of quantification of skeletal tumor burden by 18 F-fluoride PET, which performed better than visual grading for the prognostication of OS and bone marrow failure (14,22). Likewise, a small study of 14 patients with a high BSI reported short median survival after 223 RaCl 2 therapy (23).…”
Section: Discussionsupporting
confidence: 83%
“…The advanced extent of disease of the study population could have been the reason for the high incidence of hematologic toxicity relative to that in the existing literature (14,(24)(25)(26). In particular, thrombocytopenia was frequent and was associated with a complete lack of recovery within 6 mo despite the discontinuation of 223 RaCl 2 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to the ALSYMPCA trial, in which the bone scan response to treatment with 223 Ra was not evaluated, there are some studies that have focused on the utility of bone scans (scintigraphy and PET) to assess the response and toxicity associated with this therapy (36)(37)(38). In recent years, PSMA PET/CT has been making ground-breaking changes in the diagnosis and staging of PC patients, and this imaging modality is superior to choline PET (16,18,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent use of 223 Ra with chemotherapy is currently not recommended; however, the concomitant use of these treatments in selected patients seems to be safe and beneficial (36).…”
Section: Discussionmentioning
confidence: 99%